Tackling fragmentation of climate and biodiversity regimes complexes: the role ecosystem services and payment for environmental services - Hrabanski, Marie; Le Coq, Jean François (Quito, Ecuador: Flacso Ecuador, 2018)
In the realm of global governance, fragmentation is a recognized and recurrent feature and the multiple causalities underlying global governance issues along with their often cross-sectoral and cross-scale dynamics constitute major driving forces for fragmented governance. The article aims to identify the interactions between the elements of two regime complexes: climate and biodiversity. We argue that despite the different structuration and history of climate and biodiversity regime complexes, the notion of Ecosystem services, in developing specific policy instruments such as payments for environmental services, contributes to the synergy of these two complexes regimes. Indeed, ES concept has been an “integrative” and “bridging” concept that facilitated the creation of linkages between climate and biodiversity regimes complexes. First, the international diffusion of the ecosystem services concept has been possible though bringing organizations involved in both regimes complexes. Second, the market based instruments for ecosystem services and biodiversity, especially payment for environmental services has been the operational setting that enables to create at national and/or local scales the operational synergies between both issues and regimes. Payment for environmental services can achieve jointly biodiversity conservation and some mitigation and adaptation objectives.